2014
DOI: 10.2147/ijn.s56459
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific direct microtransfer of nanomaterials into Drosophila embryos as a versatile in vivo test bed for nanomaterial toxicity assessment

Abstract: Nanomaterials are the subject of intense research, focused on their synthesis, modification, and biomedical applications. Increased nanomaterial production and their wide range of applications imply a higher risk of human and environmental exposure. Unfortunately, neither environmental effects nor toxicity of nanomaterials to organisms are fully understood. Cost-effective, rapid toxicity assays requiring minimal amounts of materials are needed to establish both their biomedical potential and environmental safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Repeated experiments on possible toxic/genotoxic effects have shown that variables including core size, morphology, surface charge, and coating type are apparently key factors in modifying such effects(Arami, Khandhar, Liggitt, & Krishnan, 2015). There have been only two studies to investigate the toxicity of iron oxide NPs on small fruit flies (Drosophila)(Chen et al, 2015;Vega-Alvarez, Herrera, Rinaldi, & Carrero-Martínez, 2014) Vega-Alvarez, Herrera, Rinaldi, and Carrero-Martínez (2014). attempted to show their toxicity by introducing NPs directly into the embryonic cells through microinjection at doses of 2.5 and 5 ng, which caused a dramatic rise in cell mortality, thus concluding that FeO NPs could prove highly fatal during the initial phase of embryonic development.Similarly, Chen et al (2015) reported that relatively high doses (300-600 μg/g) of magnetite NPs impaired the survival and ability to produce live offspring (fecundity) in young females.…”
mentioning
confidence: 99%
“…Repeated experiments on possible toxic/genotoxic effects have shown that variables including core size, morphology, surface charge, and coating type are apparently key factors in modifying such effects(Arami, Khandhar, Liggitt, & Krishnan, 2015). There have been only two studies to investigate the toxicity of iron oxide NPs on small fruit flies (Drosophila)(Chen et al, 2015;Vega-Alvarez, Herrera, Rinaldi, & Carrero-Martínez, 2014) Vega-Alvarez, Herrera, Rinaldi, and Carrero-Martínez (2014). attempted to show their toxicity by introducing NPs directly into the embryonic cells through microinjection at doses of 2.5 and 5 ng, which caused a dramatic rise in cell mortality, thus concluding that FeO NPs could prove highly fatal during the initial phase of embryonic development.Similarly, Chen et al (2015) reported that relatively high doses (300-600 μg/g) of magnetite NPs impaired the survival and ability to produce live offspring (fecundity) in young females.…”
mentioning
confidence: 99%
“…On the other hand, the chicken embryo model has an advantage that the direct effect of NPs on the embryonic development can be evaluated by removing the indirect effect mediated by maternal factors easily, as reported for the results of developmental toxicity of TiO 2 -NP [185] and carbon NPs [186188]. In addition, the use of Drosophila, which has a short life span and 77% of the human disease genes [189], has just started in terms of developing cost-effective high-throughput screening methods for assessment of the developmental toxicity of NPs [190]. These animal models may provide rapid hazard assessment techniques to facilitate regulation and ensure safer NPs reach the market thereby protection future generations.…”
Section: Main Textmentioning
confidence: 99%
“…Magnetite (Fe3O4) nanoparticles, which is another form of iron oxide, was found to be highly toxic displaying 30% of viability reduction at low concentration. (Vega-Alvarez et al 2014) found that iron oxide nanoparticles synthesized by co-precipitation coated with 3-Aminopropyltriethoxysilane and iron oxide nanoparticles synthesized by thermal decomposition showed the highest mortality level in Drosophila embryos among eight different types of nanoparticles tested. The obtained data showed that iron oxide nanoparticles may act as a larvicidal agent against mosquito larvae.…”
Section: Discussionmentioning
confidence: 97%
“…Recent application of nanoparticles as insecticidal agents resulted in high mortality levels in larvae of Spodoptera littoralis (Elek et al 2010), Sitophilusoryzae (Depnath et al 2010, Anopheles subpictus and Culex quinquefasciatus (Santhoshkumar et al 2010). A limited number of studies investigated the toxicological and biological effects of different forms of iron oxide nanoparticles on Drosophila melanogaster (Alvarez et al 2014& Chen et al 2014.…”
Section: Introductionmentioning
confidence: 99%